The Development of Accepted Performance Items to Demonstrate Braille Competence in the Nemeth Code for Mathematics and Science Notation. (May 2013) - Smith, Derrick; Rosenblum, L. Penny
Introduction: The purpose of the study presented here was the initial validation of a comprehensive set of competencies focused solely on the Nemeth code. Methods: Using the Delphi method, 20 expert panelists were recruited to participate in the study on the basis of their past experience in teaching a university-level course in the Nemeth code. The Delphi method uses multiple iterations or "rounds" to develop a consensus. The panelists were given the list of competencies developed by a focus group and were asked to rank their importance and the level of resources they would expect a beginning teacher of students with visual impairments to use. With each round, the panelists were provided with the statistical results and comments on the previous round, so they could make an informed decision on their next rating. Results: Only three rounds were necessary for the panelists to reach a consensus. For writing, the panelists reached a consensus on 12 (41%) statements for importance and 17 (59%) for reference. For reading, they reached a consensus on 19 statements (66%) for importance and 23 (79%) for references. Comments from the panelists focused primarily on the fact that teachers of students with visual impairments need to use resources more often for writing to ensure the quality of their transcriptions, but that they should be able to read without resources. This difference may be due to the panelists' perception that teachers of students with visual impairments need to be more equipped to back-translate from the Nemeth code into print than to transcribe from print into the Nemeth code. Discussion: On the basis of the scoring and the comments, the panelists had different expectations for their students. These differences may have been due to their own level of understanding of the Nemeth code or mathematics in general. Implications for practitioners: This study is the first step in developing a comprehensive set of Nemeth code competencies for the field of special education for students with visual impairments. These competencies will become the benchmark for all university programs as they develop their courses on the Nemeth code. They may also be used for the framework for professional development for in-service teachers of students with visual impairments.